Bioimpedance Spectroscopy for the Detection of Fluid Overload in Chinese Peritoneal Dialysis Patients - Kwan, Bonnie Ching-Ha (Multimed Inc, 2014)
♦ Background: Fluid overload probably contributes to the cardiovascular risk of peritoneal dialysis (PD) patients. We studied the relationship between over-hydration as determined by bioimpedance spectroscopy and dialysis adequacy, nutritional status, and arterial stiffness in Chinese PD patients. ♦ Methods: We studied 122 asymptomatic prevalent PD patients: bioimpedance spectroscopy, arterial pulse wave velocity, dialysis adequacy and nutritional status were determined. ♦ Results: Of the 122 patients, 88 (72.1%) had over-hydration of ≥ 1 L, while 25 (20.5%) were ≥ 5 L. Over-hydration significantly correlated with total body water (r = 0.474, p < 0.001) and extracellular water (r = 0.755, p < 0.001). Over-hydration was more severe in male and diabetic patients, and significantly correlated with Charlson’s comorbidity score, blood pressure, body mass index, body weight, peritoneal transport characteristics, and carotid-femoral pulse wave velocity. Over-hydration significantly correlated with Kt/V (r = -0.287, p = 0.016), serum albumin level (r = -0.465, p < 0.001) and malnutrition inflammation score (r = 0.410, p = 0.006), but not residual renal function. ♦ Conclusion: Over-hydration is common in asymptomatic Chinese PD patients. The degree of over-hydration is particularly pronounced in patients who are inadequately dialyzed, have multiple comorbid conditions and low serum albumin levels. Over-hydration is associated with high blood pressure and arterial stiffness, and may contribute to the excessive risk of cardiovascular disease in this group of patients.